PowerCAD CE. - Snoonian, Deborah (Architectural Record, 2005)
This article focuses on PowerCAD introduced by GiveMePower Corp. PowerCAD is an AutoCAD- compatible program for mobile and wireless devices like cell phones, handheld organizers, and tablet PCs. The latest release features one-button e-mailing, DWF file exporting, and enhanced support for connecting with Bluetooth-equipped wireless devices. It also allows users to add voice notes to drawings.